The Social Construction of Disability in Argentina: Some Key Points - Venturiello, María Pía (2023)
The Argentinian State has transitioned from a biomedical approach to a rightsbased approach to disability. However, structural barriers and non-compliance with regulations have meant that changes that are necessary for the dignified lives of persons with disabilities are not being realised. Here we will focus on access to health, education and personal assistance.